THE MEDIATING ROLE OF GREEN WORK COMMITMENT IN THE RELATIONSHIP BETWEEN GREEN HR PRACTICES, AI ELEMENTS, AND ENVIRONMENTAL SUSTAINABILITY: A QUANTITATIVE ANALYSIS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
We examined the role that Green Work Commitment plays in the context of green HR practices, such as green hiring, green compensation, green training, AI components, and organisational sustainability. It is a quantitative research method that uses questionnaires as a data-collecting tool. The study population was the study population of employees associated with multinational corporations and essential sectors in Pakistan, such as Pakistan International Airlines, Procter & Gamble Pakistan, banks, educational institutions, and IT organisations. Likewise, key organisations such as Navoi Mining and Metallurgy Combinat JSC, POSCO International Textile, LUKOIL Uzbekistan Operating Company, Nestlé Uzbekistan, Huawei Uzbekistan, various banks, educational institutions, as well as the IT sector, collected data from Uzbekistan. In both cases, quantitative methods were used, and random and convenience sampling were used to elicit 373 responses. Descriptive statistics were performed in SPSS version 23 (mean, rates, and standard deviation), and inferential statistics in Smart PLS version 3.0. Based on these goals, 12 hypotheses were developed to investigate the relationships between green HR practices and environmental sustainability. Considering these hypotheses, ten had strong backing, while two had less strength.This study adds to the expanding body of information on Green HR practices by emphasising the mediating function of green work commitment in promoting environmental sustainability inside multinational firms in Pakistan. In this study, we outline the path for future research into the broader implications of Green HR practices for sustaining organisations across regions and industries. It would be interesting to study how green HR approaches evolve alongside AI aspects in future research, emphasising how employee engagement and organisational success are impacted by green work commitments. Furthermore, an analysis of how leadership and company culture impact green HR policies may provide more insight. To better understand how these techniques are applicable globally, a comparison can be made between emerging and developing economies.